Small-Scale Soil Microbial Community Heterogeneity Linked to Landform Historical Events on King George Island, Maritime Antarctica - Zhang, Yumin; Lu, Lu; Chang, Xulu; Jiang, Fan; Gao, Xiangdong; Yao, Yifeng; Li, Chengsen; Cao, Shunan; Zhou, Qiming; Peng, Fang (Frontiers in Microbiology, 2018)
Although research on microbial biogeography has made great progress in the past decade, distributions of terrestrial microbial communities in extreme environments such as Antarctica are not well understood. In addition, knowledge of whether and how historical contingencies affect microbial distributions at small spatial scales is lacking. Here, we analyzed soil-borne microbial (bacterial, archaeal, and fungal) communities in 12 quadrat plots around the Fildes Region of King George Island, maritime Antarctica, and the communities were divided into two groups according to the soil elemental compositions and environmental attributes of Holocene raised beach and Tertiary volcanic stratigraphy. Prokaryotic communities of the two groups were well separated; the prokaryotic data were primarily correlated with soil elemental compositions and were secondly correlated with environmental attributes (e.g., soil pH, total organic carbon, 〖NO〗_3^-, and vegetation coverage; Pearson test, r = 0.59 vs. 0.52, both P < 0.01). The relatively high abundance of P, S, Cl, and Br in Group 1 (Holocene raised beach site) was likely due to landform uplift. Lithophile-elements (Si, Al, Ca, Sr, Ti, V, and Fe) correlated with prokaryotic communities in Group 2 may have originated from weathering of Tertiary volcanic rock. No significant correlations were found between the fungal community distribution and both the soil elemental composition and environmental attributes in this study; however, Monte Carlo tests revealed that elements Sr and Ti, soil pH, sampling altitude, and moss and lichen species numbers had significant impacts on fungal communities. The elements and nutrients accumulated during the formation of different landforms influenced the development of soils, plant growth, and microbial communities, and this resulted in small-scale spatially heterogeneous biological distributions. These findings provide new evidence that geological evolutionary processes in the Fildes Region were crucial to its microbial community development, and the results highlight that microbial distribution patterns are the legacies of historical events at this small spatial scale. Based on this study, the ice-free regions in maritime Antarctica represent suitable research sites for studying the influence of geomorphological features on microbial distributions, and we envision the possibility of a site-specific landform assignment through the analysis of the soil prokaryotic community structure.